Deficiency of T-regulatory cells exaggerates angiotensin II-induced microvascular injury by enhancing immune responses. Issue 1 (January 2016) - Mian, Muhammad Oneeb Rehman; Barhoumi, Tlili; Briet, Marie; Paradis, Pierre; Schiffrin, Ernesto L.
Abstract : Aims: T-regulatory lymphocyte (Treg) adoptive transfer prevented angiotensin (Ang) II-induced hypertension and microvascular injury. Scurfy mice are deficient in Treg because of a mutation in the transcription factor forkhead box P3 ( Foxp3 ) gene. Enhanced Ang II effects in the absence of Treg would unambiguously demonstrate their vascular protective role. We hypothesized that adoptive transfer of Scurfy vs. wild-type T cells will exacerbate Ang II-induced microvascular damage in T and B-cell-deficient recombination-activating gene 1 ( Rag1 ) knockout mice. Methods and results: Rag1 knockout mice were injected with vehicle, 10 7 T cells from wild-type or Scurfy mice or 10 6 wild-type Treg alone or in combination with Scurfy T cells, and then infused or not with Ang II (490 ng/kg per min, subcutaneous) for 14 days. Ang II increased SBP in all the groups, but DBP only in wild-type and Scurfy T-cell groups. Ang II-induced endothelial dysfunction and oxidative stress in perivascular adipose tissue (PVAT) of mesenteric arteries of the wild-type T-cell group, whereas these were exaggerated in the Scurfy T-cell group. Ang II enhanced microvascular remodeling and stiffness in vehicle and Scurfy T-cell groups. Ang II increased monocyte chemotactic protein-1 expression in the vascular wall and PVAT, monocyte/macrophage infiltration and proinflammatory polarization in PVAT and the renal cortex, and T-cell infiltration in the renal cortex only in the Scurfy T-cell group. Treg coinjection in the vehicle and Scurfy T-cell groups prevented or reduced the effects of Ang II. Conclusion: FOXP3 + Treg deficiency exaggerates Ang II-induced microvascular injury by modulating innate and adaptive immune responses. Abstract : Supplemental Digital Content is available in the text